Imposition of Zero Percent Royalty for Mining Companies Increasing the Added-Value of Coal in Indonesia - Pawestri, Widhayani Dian; Salim, Katherine Abidea; Suminaring Aditya, Kukuh Leksono (Magister of Law, Faculty of Law, University of Mataram, 2025)
Indonesia is a country rich in natural resources. The 1945 Constitution provides a mandate for the Government to manage natural resources within the jurisdiction of the State for the greatest prosperity of the people. In mining sectors, Indonesian Government requires mining companies to conduct activities to add value to coal that will provide more benefit for low-quality coal and reduce carbon emissions from the use of processed coal. To support this activity, the Government imposed a zero percent royalty policy. The purpose of this study is to analyze changes in royalty policy in Indonesia and to analyze the most beneficial profit-sharing system to be used in Indonesia. This research is legal research that uses a statutory approach, conceptual approach, and comparative approach with China and Australia to analyze the principle and regulations related to royalty and profit-sharing policies in the coal mining sector. This policy has the possibility to give impacts that will give both benefits and disadvantages that must be anticipated by the Government. The profit-sharing system that will give the maximum benefit for Indonesia is the royalty system which also reflects the principle of State control of natural resources as mandated by the 1945 Constitution